2010
DOI: 10.1002/jcp.22246
|View full text |Cite
|
Sign up to set email alerts
|

PTP1B deficiency enhances liver growth during suckling by increasing the expression of insulin‐like growth factor‐I

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is a negative regulator of insulin and tyrosine kinase growth factor signaling. We have recently demonstrated that PTP1B deficiency increases GLUT2/insulin receptor (IR) A complexes and glucose uptake in suckling, but not adult, primary hepatocytes. Herein we have investigated intrahepatic glucose utilization in 3-5 days old wild-type and PTP1B(-/-) mice. PTP1B deficiency decreased glycogen, lactate, and pyruvate content in the livers from suckling mice. Conversely, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…SHP1 and SHP2 present no age difference, while PTP1B content is elevated in one-week mice and decreases thereafter. Our results suggest that PTP1B could be participating in the rapid dephosphorylation of activated substrates at early ages, thus impeding GH signaling, in agreement with recent observations in which STAT5 phosphorylation was found augmented in PTP1B -/-3 day old mice [64], and that rapid STAT5 dephosphorylation was described when PTP1B was overexpressed [14]. Mice lacking functional SHP1, SHP2 or PTP1B do not present enhanced growth [65][66][67], while mice lacking the PTPH1 catalytic domain exhibit a modest increment in body weight, especially in male mice.…”
Section: Discussionsupporting
confidence: 93%
“…SHP1 and SHP2 present no age difference, while PTP1B content is elevated in one-week mice and decreases thereafter. Our results suggest that PTP1B could be participating in the rapid dephosphorylation of activated substrates at early ages, thus impeding GH signaling, in agreement with recent observations in which STAT5 phosphorylation was found augmented in PTP1B -/-3 day old mice [64], and that rapid STAT5 dephosphorylation was described when PTP1B was overexpressed [14]. Mice lacking functional SHP1, SHP2 or PTP1B do not present enhanced growth [65][66][67], while mice lacking the PTPH1 catalytic domain exhibit a modest increment in body weight, especially in male mice.…”
Section: Discussionsupporting
confidence: 93%
“…The molecular mechanism responsible of this effect likely involve tyrosine kinase receptors such as EGF receptor, HGF receptor (Met) or insulin-like growth factor-1 receptor (IGF1R), implicated in the control of proliferation and survival of hepatocytes, all of them dephosphorylated and inactivated by PTP1B [49] . In this regard, we have described that PTP1B deficiency increases liver growth enhancing the STAT5B/IGF1/IGF1R axis during suckling [50] . In addition, the faster recovery of PTP1BKO livers against NASH damage might also involve an effect on hepatic oval cells since their proliferation positively correlates with the extent of liver damage [51] .…”
Section: Discussionmentioning
confidence: 94%
“…Likewise other researchers conducted studies on the PTP-1B KO mice and observed significant growth disturbances. Escrivá et al [ 107 ] stated that PTP-1B KO mice had higher body and liver weight at the 3rd day after birth. The same authors showed that PTP-1B KO mice were characterized by the increased STAT5β phosphorylation and, in consequence, the increased level of the IGF-1 in liver was stated.…”
Section: Ghr-jak2-stat Inhibitorsmentioning
confidence: 99%